Betamethasone latency period and neonatal hypoglycemia in term infants - Lauren A. Buckley; Briana Clifton; Katelyn M. Tessier; Connor Demorest; Raghavendra B. Rao; Sarah A. Wernimont (The Journal of Maternal-Fetal & Neonatal Medicine)
Introduction Infants exposed to antenatal betamethasone (BMZ) between 34.0 and 36.6 weeks gestational age (GA) have increased risk for neonatal hypoglycemia, a known cause of brain injury. While a shorter latency period between BMZ administration and delivery is associated with an increased risk of neonatal hypoglycemia in late preterm infants, the impact of the BMZ latency period on neonatal hypoglycemia in infants born at term (≥37 weeks) has not been previously characterized. Term infants without additional risk factors such as growth restriction or maternal diabetes are not routinely screened and may be at risk for unrecognized neonatal hypoglycemia. The purpose of this study was to determine whether the latency period from antenatal BMZ administration to delivery impacts the incidence of neonatal hypoglycemia in term infants.Methods This retrospective cohort study analyzed maternal–infant dyads from the University of Minnesota Obstetric Measures database (January 2017–August 2023) who received BMZ during pregnancy and delivered at ≥37 weeks (N = 758). The primary outcome was incidence of early neonatal hypoglycemia, defined as a blood glucose level <40 mg/dL within 48 h of birth, in neonates exposed to BMZ <14 days (recent BMZ; N = 161) vs. >14 days (remote BMZ; N = 597) prior to delivery. Secondary outcomes included incidence of severe neonatal hypoglycemia (blood glucose level <25 mg/dL within 48 h of birth) and treatment for neonatal hypoglycemia with dextrose gel or IV dextrose. Demographics, pregnancy characteristics, neonatal characteristics, and outcomes were summarized by time from last dose of BMZ to delivery.Results The most common indication for BMZ was pre-eclampsia/pregnancy-induced hypertension in the recent BMZ group and preterm labor with intact membranes in the remote BMZ group (p < .001). Maternal diabetes status did not differ between groups. The recent BMZ group had lower median GA at birth (37.1 vs. 38.4 weeks, p < .001) and lower birth weight (3.03 vs. 3.29 kg, p < .001). The percentage of neonates classified as small for GA or large for GA was similar between groups. Approximately 30% of the neonates had a documented glucose measurement within 48 h of birth. The incidence of early neonatal hypoglycemia, severe hypoglycemia, and treatment for hypoglycemia with dextrose gel or IV dextrose did not differ between infants exposed to recent BMZ vs. those exposed to remote BMZ.Discussion In this cohort of term infants, a shorter latency period between BMZ administration and delivery was not associated with increased incidence or treatment of hypoglycemia. However, the rate of hypoglycemia screening was low in both groups and rates of undiagnosed hypoglycemia in BMZ-exposed term neonates remain unknown. Prospective longitudinal studies aimed at characterizing the risk of hypoglycemia in term infants exposed to BMZ would be beneficial to inform hypoglycemia screening practices in BMZ-exposed neonates.